Using accession to investigate accessibility induced social exclusion in Edinburgh and the Lothians - Weir, Andrew (My University, 2008)
An exploratory analysis of accessibility-based social exclusionary mechanisms in Edinburgh and the Lothians is presented, with the aim of highlighting the benefits of a technique that incorporates socio-geodemographic variables. Accession software is used to produce accessibility times to three different types of services. Postcode centroids are used to represent centres of population, while the Navteq road network and latest public transport timetables are used to model the transport networks. In addition, census derived socio-geodemographic variables are included in the analysis. This allows results to be tested within a framework of scenarios, designed to highlight areas at greatest potential risk from accessibility-based social exclusion. Results highlight the benefits of using such an approach, demonstrating that accessibility analysis alone is insufficient to highlight excluded areas. Examples show potentially excluded areas in Dunbar, Haddington and Dalkeith, as opposed to the large rural areas with the poorest accessibility levels. It is suggested that such techniques could be adopted, in conjunction with census 2011 data, to create a geo-database containing a multitude of variables that should include accessibility values. Making this an online resource could enable an unprecedented breakthrough in investigating and disseminating accessibility based exclusion problems.
Keywords: Accessibility; social exclusion; GIS; MSc Geographical Information Science